The Effectiveness of the Snug Vest on Stereotypic Behaviors in Children Diagnosed With an Autism Spectrum Disorder. (May 2014) - Watkins, Nicholas; Sparling, Elizabeth
Various reviews of the effects of sensory integration therapy (SIT) have concluded that such interventions fail to reduce stereotypy. However, a new, and as yet untested, SIT iteration, an inflatable wearable vest known as the Snug Vest purports to decrease such repetitive behavior. In the current study, three children who emitted different forms of stereotypy participated in an alternating treatments design in which each participant wore a fully inflated vest and either a fully deflated vest or no vest. The results of the study show that the Snug Vest failed to reduce any participants' stereotypy. We highlight our findings in the context of professional practice and discuss several potential limitations.